SVG Essentials - Eisenberg, J. David; Bellamy-Royds, Amelia (O'Reilly Media, 2015)
SVG Essentials takes you through SVG's capabilities, beginning with simple line drawings and moving through complicated features such as filters, transformations, gradients, and patterns. This thoroughly updated edition includes expanded coverage of animation, interactive graphics, and scripting SVG.